Moda e identidade: uma análise das manifestações digitais das It girls - (:unkn) unknown (Universidade Federal do Pampa, 2014)
This research aims to investigate the role of fashion as ephemeral to represent the identity of the it girls in order to find out if the element changes taking place in the fashion world, assist in the representation of identity. The guiding research question and aims to observe how the ephemeral nature of fashion influences in the representation of the identity of it girls through digital manifestations. Stupid Girls Blog, Blog and Blog Thassia Style Olivia Palermo: To this end, three fashion blogs were studied. The analysis that was performed was based on the semiotic square and actantial model Greimas.
Keywords: Moda; Identidade social; Blogs; Internet; Fashion; CNPQ::CIENCIAS SOCIAIS APLICADAS